Exercise Evaluation and Prescription - Cortis, Cristina; Fusco, Andrea; Foster, Carl (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is a reprint of articles from the Special Issue published online in the open access journal Journal of Functional Morphology and Kinesiology (ISSN 2411-5142) available at https://www.mdpi.com/journal/jfmk/special_issues/Exercise_Evaluation